A genetic comparison of sympatric anadromous and resident Atlantic salmon. Issue 2 (22nd December 2014) - Adams, Blair K.; Cote, David; Hutchings, Jeffrey A.
Abstract: Many studies have identified the importance of local adaptation in Atlantic salmon ( Salmo salar ) and the strong genetic differences that exist between allopatric or parapatric resident and anadromous populations. However, as truly sympatric migratory phenotypes of Atlantic salmon have not been studied, it remains unclear whether distinct genotypes previously associated with life history differences are maintained through reproductive isolation and subsequent genetic drift or through natural selection induced by different life history requirements. In this study, sympatric anadromous and resident Atlantic salmon were sampled from three Newfoundland (Canada) watersheds to evaluate the genetic divergence of these life history forms. Eight microsatellite loci were used to quantify genetic variation within and among populations. Metrics of genetic differentiation (exact tests for population differentiation, pairwise θ values) provide no evidence of genetic differentiation between some sympatric anadromous and resident phenotypes within a system with no history of segregation. In the remaining two watersheds, the observed differentiation appears to be a consequence of historical segregation rather than life history form. Nonetheless, these differences have been maintained in contemporary times for several generations. At broader spatial scales, resident salmon were more genetically divergent from one another than anadromous life history forms and were more closely related to anadromous salmon from within their watershed than to resident salmon from other watersheds. The study indicates that both life history forms can be maintained within a single population, but that sympatric populations of different life histories can maintain genetic differences for at least several generations after being reconnected.